The Impact of Entrepreneurship on Economic Performance in Indonesia - Kadarusman, Yohanes (UI Scholars Hub, 2020)
Entrepreneurship is claimed to have a positive and significant effect on economic growth in developed countries, but less so in developing countries. Using the growth model, this study examines the impact of entrepreneurship on economic performance in Indonesia as indicated by economic growth and income per-capita from 1985 to 2017. The estimation result confirms the non-significant effect of the growth of entrepreneurial ventures on the growth of GDP per-capita. However, the accumulation of the ventures has a positive and significant effect on the level of GDP per capita. The different typology of entrepreneurial ventures in Indonesia provides some insight to explain the finding, namely: scale does matter. Indonesia already has abundant micro-scale entrepreneurs, but it has only a limited amount of small-scale entrepreneurs, and even fewer medium or large-scale entrepreneurs. This finding contributes to a better understanding of the statistically non-significant impact of entrepreneurship on economic growth in developing countries. This study also suggests that entrepreneurship policy in Indonesia should focus more on facilitating micro-scale ventures to continuously develop toward small, medium, and ultimately large-scale enterprises rather than on creating start-ups.